Magneto-optical rotation of heavy-metal oxide glasses - Pedroso, C. B.; Munin, Egberto; Villaverde, A. Balbin; Aranha, N. [UNESP]; Reynoso, V. C. Solano; Barbosa, L. C. (Elsevier, 1998)
Magneto-optical rotation was measured at room temperature for glasses containing Bi2O3-CdO-GeO2 (BCG), and Bi2O3-PbO-GeO2-B2O3 (BPGP). A pulsed magnetic field between 50 and 80 KG was used to measure Faraday rotation at 632.8 nm as a function of the concentration of Bi and Cd for BCG and Bi and Pb for BPGB. Verdet constant as high as 0.162 min G-1 cm-1 at 632.8 nm for the BPGB sample with the highest concentrations of Bi and Cd was found. Verdet constant increases linearly with the heavy-metal concentration for the BPGB whereas it reaches some saturation for the BCG system. Measurements of the magneto-optical rotation at other wavelengths in the visible and the refractive index at 632.8 nm are also reported. © 1998 Elsevier Science B.V. All rights reserved.
Keywords: Bismuth compounds; Cadmium compounds; Composition effects; Faraday effect; Germanium compounds; Lead compounds; Optical rotation; Oxides; Refractive index; Verdet constant; Optical glass